2017
DOI: 10.5152/tjg.2017.16636
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing esophageal squamous cell papillomas for the presence of human papilloma virus

Abstract: Background/Aims: Human Papilloma Virus (HPV) infection can be a predisposing condition for the development of squamous cell papilloma (SCP) of the esophagus, which can progress to dysplasia and to carcinoma as a result of chronic infection. The aim of the present study was to search for the presence of HPV in the esophageal SCP, and to genotype the detected HPV. Materials and Methods: Data from patients with definite diagnosis of SCP of the esophagus were identified from pathology records for two years period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…A study of 38 patients with ESP from Turkey identified seven lesions infected with HPV. Of them, four were low risk (types 6 and 81) and three were high risk (types 16, 18 and 31) . In a smaller study in Mexico, there were 14 HPV‐positive ESPs, of which 10 were infected with low‐risk HPV (types 6 and 11) and two were infected with high‐risk HPV (type 16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 38 patients with ESP from Turkey identified seven lesions infected with HPV. Of them, four were low risk (types 6 and 81) and three were high risk (types 16, 18 and 31) . In a smaller study in Mexico, there were 14 HPV‐positive ESPs, of which 10 were infected with low‐risk HPV (types 6 and 11) and two were infected with high‐risk HPV (type 16) .…”
Section: Discussionmentioning
confidence: 99%
“…Of them, four were low risk (types 6 and 81) and three were high risk (types 16, 18 and 31). 7 In a smaller study in Mexico, there were 14 HPV-positive ESPs, of which 10 were infected with low-risk HPV (types 6 and 11) and two were infected with high-risk HPV (type 16). 8 More data are needed to better understand the patterns of HPV infection in ESPs as well as their potential oncogenic role.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Tiftikçi et al 21 analyzed esophageal SCPs for the presence of HPV. Patients with a definite diagnosis of SCP of the esophagus were identified from pathology records for a 2-year period.…”
Section: Is There An Association Between Hpv and Esophageal Papillomas?mentioning
confidence: 99%
“…E sophageal cancer is the eighth most common cause of cancer and the sixth most common cancer-related death 1 . In Brazil, excluding non-melanoma skin cancer, it is the sixth most incident among men and thirteenth among women 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Its prognosis is poor, with a survival rate of around 20% over five years. The most common histological type in the world is still squamous cell carcinoma, with geographical and ethnic variations, followed by adenocarcinoma 1 . The risk factors for the development of esophageal squamous cell carcinoma are not well defined, with the use of alcohol and tobacco accountable as the main etiological factors.…”
Section: Introductionmentioning
confidence: 99%